Angiogenesis in salivary gland tumors: from clinical significance to treatment. (June 2015) - Theocharis, Stamatios; Gribilas, George; Giaginis, Constantinos; Patsouris, Efstratios; Klijanienko, Jerzy
<x xml:space="preserve">Abstract</x> Introduction: Salivary gland tumors (SGTs) represent a rare cancer entity, consisting of various morphological features that complicate diagnosis. Their diversity in terms of morphology and clinical course makes defining risk factors difficult, while the molecular steps responsible for SGT development remain unclear. Angiogenesis, a hallmark of cancer development, is considered as an attractive target. Areas covered: This review aims to summarize the available research regarding angiogenesis in SGTs from clinical significance to treatment options. Expert opinion: The available data suggest that microvessel density (MVD) evaluation may be capable of discriminating between benign and malignant SGTs, while the use of CD105 antibody seems to be the most suitable. Substantial evidence also suggests that MVD and VEGF expression could be used as prognostic factors in malignant SGTs. Although several agents have shown antiangiogenic activities in adenoid cystic carcinoma cells and xenograft tumors, limited effectiveness in the existing clinical trials was noted. Further studies are strongly recommended for the validation of already well-known and the identification of novel prognostic and predictive angiogenic markers. There is also a strong demand for relatively larger cohorts, homogenous samples referring to same histological SGT subtypes and including an equivalent number of low- and high-grade SGTs.